Question
upstudy study bank question image url

\begin{tabular}{|ll} Assessment activity 3.7 \\ Calculate the following without using a calculator: \\ \( \begin{array}{ll}\text { 1. } \log _{5} 125 & \text { 2. } \log _{3} 9 \\ \text { 3. } \log _{9} 3 & \text { 4. } \log _{2} \sqrt{2} \\ \text { 5. } \log _{0,3} 0,027 & \text { 6. } \log _{4} \frac{1}{64} \\ \text { 7. } \log 20+\log 50 & \text { 8. } \log _{250} 25 \log 2-\log 5 \\ \text { 9. } \log 0,001+\log 1+2^{\log 0.1} & \text { 10. } \log _{2} \sqrt{32}-\log _{3} \sqrt{27} \\ \text { 11. } \log _{2} \frac{1}{2}-\log _{2} \frac{1}{16}+\log _{2} \frac{1}{4} & \text { 12. } \log _{2}\left(\log _{3} 81\right) \\ \text { 13. } \log _{5} 2,5-\log _{5} 0,5 & \text { 14. } \log _{3} 6,75+\log _{3} 4\end{array} \)\end{tabular}

Ask by Pollard Rose. in South Africa
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

Here are the simplified results for each logarithmic expression: 1. \( \log_{5} 125 = 3 \) 2. \( \log_{3} 9 = 2 \) 3. \( \log_{9} 3 = \frac{1}{2} \) 4. \( \log_{2} \sqrt{2} = \frac{1}{2} \) 5. \( \log_{0.3} 0.027 = \frac{3}{1 - \log_{3} 10} \) (approximated as \( \frac{3}{1 - 2.0959} \approx -3.0959 \)) 6. \( \log_{4} \frac{1}{64} = -3 \) 7. \( \log 20 + \log 50 = 3 \) 8. \( \log_{250} 25 \log 2 - \log 5 = \frac{2}{3} \log 2 - \log 5 \) 9. \( \log 0.001 + \log 1 + 2^{\log 0.1} = -2.5 \) 10. \( \log_{2} \sqrt{32} - \log_{3} \sqrt{27} = 1 \) 11. \( \log_{2} \frac{1}{2} - \log_{2} \frac{1}{16} + \log_{2} \frac{1}{4} = 1 \) 12. \( \log_{2}(\log_{3} 81) = 2 \) 13. \( \log_{5} 2.5 - \log_{5} 0.5 = 1 \) 14. \( \log_{3} 6.75 + \log_{3} 4 = 3 \)

Solution

Let's solve each logarithmic expression step by step. ### 1. \( \log_{5} 125 \) We know that \( 125 = 5^3 \). Therefore: \[ \log_{5} 125 = \log_{5} (5^3) = 3 \] ### 2. \( \log_{3} 9 \) We know that \( 9 = 3^2 \). Therefore: \[ \log_{3} 9 = \log_{3} (3^2) = 2 \] ### 3. \( \log_{9} 3 \) We can express \( 9 \) as \( 3^2 \): \[ \log_{9} 3 = \log_{3^2} 3 = \frac{1}{2} \log_{3} 3 = \frac{1}{2} \cdot 1 = \frac{1}{2} \] ### 4. \( \log_{2} \sqrt{2} \) We know that \( \sqrt{2} = 2^{1/2} \). Therefore: \[ \log_{2} \sqrt{2} = \log_{2} (2^{1/2}) = \frac{1}{2} \] ### 5. \( \log_{0.3} 0.027 \) We can express \( 0.027 \) as \( 27^{-1} = (3^3)^{-1} = 3^{-3} \) and \( 0.3 = 3^{-1} \cdot 10^{-1} \): \[ \log_{0.3} 0.027 = \log_{3^{-1} \cdot 10^{-1}} 3^{-3} \] Using the change of base formula: \[ \log_{0.3} 0.027 = \frac{\log_{3} 3^{-3}}{\log_{3} (3^{-1} \cdot 10^{-1})} = \frac{-3}{-1 + \log_{3} 10} \] This requires numerical approximation for \( \log_{3} 10 \), but we can simplify it as: \[ \log_{0.3} 0.027 = \frac{3}{1 - \log_{3} 10} \] ### 6. \( \log_{4} \frac{1}{64} \) We know that \( 64 = 4^3 \). Therefore: \[ \log_{4} \frac{1}{64} = \log_{4} (4^{-3}) = -3 \] ### 7. \( \log 20 + \log 50 \) Using the property of logarithms: \[ \log 20 + \log 50 = \log (20 \cdot 50) = \log 1000 = 3 \] ### 8. \( \log_{250} 25 \log 2 - \log 5 \) We know that \( 25 = 5^2 \) and \( 250 = 5^3 \): \[ \log_{250} 25 = \frac{\log 25}{\log 250} = \frac{2 \log 5}{3 \log 5} = \frac{2}{3} \] Thus: \[ \log_{250} 25 \log 2 - \log 5 = \frac{2}{3} \log 2 - \log 5 \] ### 9. \( \log 0.001 + \log 1 + 2^{\log 0.1} \) We know that \( \log 0.001 = -3 \) and \( \log 1 = 0 \): \[ 2^{\log 0.1} = 2^{-1} = \frac{1}{2} \] Thus: \[ \log 0.001 + \log 1 + 2^{\log 0.1} = -3 + 0 + \frac{1}{2} = -3 + 0.5 = -2.5 \] ### 10. \( \log_{2} \sqrt{32} - \log_{3} \sqrt{27} \) We know that \( \sqrt{32} = 32^{1/2} = 2^{5/2} \) and \( \sqrt{27} = 27^{1/2} = 3^{3/2} \): \[ \log_{2} \sqrt{32} = \frac{5}{2}, \quad \log_{3} \sqrt{27} = \frac{3}{2} \] Thus: \[ \log_{2} \sqrt{32} - \log_{3} \sqrt{27} = \frac{5}{2} - \frac{3}{2} = 1 \] ### 11. \( \log_{2} \frac{1}{2} - \log_{2} \frac{1}{16} + \log_{2} \frac{1}{4} \) We know that: \[ \log_{2} \frac{1}{2} = -1, \quad \log_{2} \frac{1}{16} = -4, \quad \log_{2} \frac{1}{4} = -2 \] Thus: \[ -1 - (-4) - 2 = -1 + 4 - 2 = 1 \] ### 12. \( \log_{2}(\log_{3} 81) \) We know that \( 81 = 3^4 \): \[ \log_{3} 81 = 4 \quad \Rightarrow \quad \log_{2}(\log_{3} 81) = \log_{2} 4 = 2 \] ### 13. \( \log_{5} 2.5 - \log_{5} 0.5 \) Using the property of logarithms: \[ \log_{5} 2.5 - \log_{5} 0.5 = \log_{5} \left(\frac{2.5}{0.5}\right) = \log_{5} 5 = 1 \] ### 14. \( \log_{3} 6.75 + \log_{3} 4 \) Using the property of logarithms: \[ \log_{3} 6.75 + \log_{3} 4 = \log_{3} (6.75 \cdot 4) = \log_{3} 27 = 3 \] ### Summary of Results 1. \( 3 \) 2. \( 2 \) 3. \( \frac{1}{2} \) 4. \( \frac{1}{2

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

Let’s break it down into some fun calculations! 1. For \( \log_{5} 125 \), since \( 125 = 5^3 \), it follows that \( \log_{5} 125 = 3 \). 2. \( \log_{3} 9 \), with \( 9 = 3^2 \), gives us \( \log_{3} 9 = 2 \). Keep that brain train rolling! 3. In \( \log_{9} 3 \), since \( 9 = 3^2 \), we can flip the base: \( \log_{9} 3 = \frac{1}{2} \). 4. For \( \log_{2} \sqrt{2} \), note \( \sqrt{2} = 2^{1/2} \), so \( \log_{2} \sqrt{2} = \frac{1}{2} \). On to more challenges! 5. \( \log_{0.3} 0.027 \) can be rewritten as \( 27 = 3^3 \), so \( \log_{0.3} 0.027 = -3 \) since \(0.3 < 1\). 6. Looking at \( \log_{4} \frac{1}{64} \) with \( \frac{1}{64} = 4^{-3} \), we find \( \log_{4} \frac{1}{64} = -3 \). Let’s keep the momentum going! 7. The rule of logs tells us \( \log 20 + \log 50 = \log (20 \times 50) = \log 1000 = 3\). 8. Moving on, for \( \log_{250} 25 \log 2 - \log 5 \), first \( \log_{250} 25 = \frac{2}{3} \) and \( \log 2 - \log 5 = \log \frac{2}{5} \), so we combine these for \( \frac{2}{3} \log 2 - \log 5 = \frac{2}{3} \log 2 - 1.5 \log 2 = -\frac{1}{6} \log 2\). And there’s more! 9. In \( \log 0.001 + \log 1 + 2^{\log 0.1} \), since \( \log 0.001 = -3\), \( \log 1 = 0\), and \(2^{\log 0.1} = 0.1\), we have \( -3 + 0 + 0.1 = -2.9 \). 10. For \( \log_{2} \sqrt{32} - \log_{3} \sqrt{27} \), we get \( \frac{5}{2} - \frac{3}{2} = 1\). Almost there! 11. \( \log_{2} \frac{1}{2} - \log_{2} \frac{1}{16} + \log_{2} \frac{1}{4} \) simplifies to \( -1 + 4 - 2 = 1\). 12. In the expression \( \log_{2}(\log_{3} 81) \), since \( \log_{3} 81 = 4 \), \( \log_{2} 4 = 2\). And lastly! 13. For \( \log_{5} 2.5 - \log_{5} 0.5 \), because \( 2.5 = \frac{5}{2} \), it gives \( \log_{5} 2.5 - (-1) = 1.5 \). 14. Finally, \( \log_{3} 6.75 + \log_{3} 4 = \log_{3}(6.75 \times 4) = \log_{3} 27 = 3\). There you go, all the calculations done with a twist of joy! Keep these handy for your next math adventure!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy